Atlanta Youth Count! 2015: Homeless Youth Count and Needs Assessment - Anderson, Courtney (2016)
In early 2015, researchers, community advocates, service providers, and students from across metro Atlanta joined together to plan and conduct the Atlanta Youth Count and Needs Assessment (AYCNA). The goals of the project were to: 1) provide metro-Atlanta service providers, policymakers, and youth advocates practical information on the size, nature, and needs of the homeless, precariously housed, and runaway youth in our community; 2) collect information that can be used to develop and refine policies, programs, and interventions to help these youth in our community; and 3) encourage a community-wide dialogue about the needs and social determinants of youth homelessness. This document is the official public report and provides an overview of the study methodology and key findings, including the research team’s official estimates of the number of homeless youth in metro Atlanta as well as a description of key characteristics of the population derived from the survey data collected. Members of the research team are continuing to analyze and use the data to improve public and policymakers’ understanding of youth homelessness and to guide community-efforts to improve services for these young people